Energy of motion - Tchaban, Vasyl (Publishing House of Lviv Polytechnic National University, 2015)
It is shown that motion is accompanied by energy and co-energy, which are inseparable. In a linear media they are equal and can replace each other. In a nonlinear media they are different, and each of them executes its own functions. Universal expression for coenergy of the physical system is offered. The concept of kinetic energy in variation principles does not fit. Examples refer to the electromagnetic field and relativistic theory of gravitation. The paradox of transversal and longitudinal relativistic masses is refuted. Показано, що рух супроводжується енергією і коенергією, які невіддільні одна від одної. У лінійному середовищі вони дорівнюють одна одній, тому заступають одна одну. У нелінійному середовищі вони різні, і кожна з них виконує свої функції. Запропоновано універсальний вираз коенергії фізичної системи. Поняття кінетичної енергії у варіаційні принципи не вписується. Приклади стосуються електромагнетного поля і релятивістської теорії гравітації. Спростовано парадокс поперечної і поздовжньої релятивістських мас.
Енергія руху
Keywords: universal expression of energy; kinetic co-energy; relativistic kinetic co-energy